Provocation of sudden heart rate oscillation with adenosine exposes abnormal QT responses in patients with long QT syndrome: a bedside test for diagnosing long QT syndrome - Viskin, Sami (2005)
Aims As arrhythmias in the long QT syndrome (LQTS) are triggered by heart rate deceleration or acceleration, we speculated that the sudden bradycardia and subsequent tachycardia that follow adenosine injection would unravel QT changes of diagnostic value in patients with LQTS. Methods and results Patients (18 LQTS and 20 controls) received intravenous adenosine during sinus rhythm. Adenosine was injected at incremental doses until atrioventricular block or sinus pauses lasting 3 s occurred. The QT duration and morphology were studied at baseline and at the time of maximal bradycardia and subsequent tachycardia. Despite similar degree of adenosine-induced bradycardia (longest R-R 1.7 + 0.7 vs. 2.2 + 1.3 s for LQTS and controls, P = NS), the QT interval of LQT patients increased by 15.8 + 13.1%, whereas the QT of controls increased by only 1.5 + 6.7% (P<0.001). Similarly, despite similar reflex tachycardia (shortest R-R 0.58 + 0.07 vs. 0.55 + 0.07 s for LQT patients and controls, P = NS), LQTS patients developed greater QT prolongation (QTc = 569 + 53 vs. 458 + 58 ms for LQT patients and controls, P<0.001). The best discriminator was the QTc during maximal bradycardia. Notched T-waves were observed in 72% of LQT patients but in only 5% of controls during adenosine-induced bradycardia (P<0.001). Conclusion By provoking transient bradycardia followed by sinus tachycardia, this adenosine challenge test triggers QT changes that appear to be useful in distinguishing patients with LQTS from healthy controls.